Human vaccine candidates for infections caused by Klebsiella pneumoniae: A systematic review - Motamed, Hajar; Yari, Farideh; Javadirad, Etrat; Golmohammadi, Sima; Alimoradi, Saeed; Naleini, Ronak; Chegene Lorestani, Roya; Nemati Zargaran, Fatemeh; Rostamian, Mosayeb (Health science reports, 2024)
Background and Aims There are many difficulties in treating Klebsiella pneumoniae, necessitating the creation of more preventative/therapeutic measures like vaccinations. However, after numerous attempts, there is still no authorized and widely accessible vaccine. The present study aimed to systematically review published studies on K. pneumoniae vaccines in human subjects/samples. Methods To find published studies, several electronic databases, including Scopus, PubMed, Web of Science, ClinicalKey, ClinicalTrials.gov, and Cochrane Library were searched without time limitation using the appropriate keywords. Studies were scrutinized, and the information from those that met our inclusion criteria was gathered and analyzed. Results In total, 691 studies were found, of which 14 articles were included for systematic review. Bacterial lysate containing K. pneumoniae was the most studied vaccine candidate. As the main indicator of human immune responses to K. pneumoniae, antibody responses were determined by most studies. The antigen amount, the route of immunization, and the immunization schedule were varying in the studies and were chosen based on several factors such as the disease model, the vaccine type, the vaccination setting (prophylactic or therapeutic), and so on. Conclusion The majority of studies asserted that their vaccination was efficient and safe, which was demonstrated by a decrease in the rate of infections and the induction of protective antibody, cell‐dependent, and/or cytokine responses. Altogether, the information provided here will help researchers examine the K. pneumoniae vaccine candidates more closely and take future actions that will be more consistently successful.